Impact of osmotic/matric stress and heat shock on environmental tolerance induction of bacterial biocontrol agents against Fusarium verticillioides - Sartori, Melina Victoria (2010)
Bacillus amyloliquefaciens and Microbacterium oleovorans reduced Fusarium verticillioides count and decreased significantly fumonisins B1 and B2 levels in maize grains. The aims of this study were to determine the effect of water stress tolerance and heat-shock survival in cells of the biocontrol agents B. amyloliquefaciens and M. oleovorans. The aw of solid and liquid media, tryptic soy medium, was modified to 0.99, 0.98, 0.97 and 0.96 by the addition of the ionic solute NaCl and with the non-ionic solutes such as glycerol and glucose. The non-ionic solute polyethylene glycol 600 (PEG 600) was used to modify matrically solid media. Bacteria incubation was at 30ºC. After 24, 48 and 72 h of incubation samples from liquid media were spread-plate on nutrient agar medium and incubated 24 h to determine number of viable cells. The bacterial cells were harvested by centrifugation and heat treatment carried out in a water bath at 45ºC during 30 min. The viability of cells from different incubation time in liquid media showed statistically significant differences. Cells of B. amyloliquefaciens grown in liquid media amended with glycerol showed better tolerance at low aw and high survival under heat stress. These results could have important implications for optimizing and to improve formulations.